Agricultural Transformations and Their Influential Factors Revealed by Archaeobotanical Evidence in Holocene Jiangsu Province, Eastern China - Li, Haiming; Liu, Zhen; James, Nathaniel; Li, Xinsheng; Hu, Zhujun; Shi, Hongwei; Sun, Liqiang; Lu, Yong; Jia, Xin (Frontiers in Earth Science, 2021)
The development and adoption of agriculture has been investigated for decades, and remains a central topic within archaeology. However, most previous studies focus on the crop’s domestication centers lead to gaps in knowledge, particularly in transitional zones between these centers. This paper reviews published archaeobotanical evidence and historical documents to reconstruct the trajectory of agricultural systems in Holocene Jiangsu Province. Comparing these new results to paleoclimate, historical documents, and archaeological data enables us to better understand the underlying influences of past agricultural development. Our results indicate that a warm and wet climate may promoted ancient peoples to first settle in Jiangsu between 8500-6000 BP and adopt rice farming. Continuous warm and wet climate may have facilitated the rapid development and expansion of rice agriculture, ultimately contributing to large-scale human settlement in 6000-4000 BP in Jiangsu Province. Between 4000-2300 BP during a cooler and drier climate millet agriculture diffused southward, facilitating a mixed rice and millet agricultural system. This mixed farming supported widespread settlement and population growth in Jiangsu continued. After 2300 BP, political instability in north China resulted in further southeastward migration, advanced planting technology was brought about to south China, facilitating highly developed agricultural systems and rapid population expansion in Jiangsu. Population growth led to the establishment of Jiangnan as regional economic center, where people chose high-yielding rice and wheat rather than millet.